Telehealth in maternity care: benefits, barriers, and the future of digital maternity care: a narrative review - Ali, Neha; Philip, Sheeba; Rawat, Deepika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Telehealth is emerging as a vital tool in maternity care, supporting pregnant women and their families through remote healthcare services, it creates new opportunities to provide continuous, patient-centered, and accessible care. This review examines the applications, benefits, and challenges of telehealth in maternity care with a focus on its implications. A structured search strategy was conducted across PubMed Medline, Google Scholar, Research Gate, Scopus, and Science Direct. Keywords included telehealth, telemedicine, nursing, and maternity care. Relevant studies were screened and references cross-checked to capture additional evidence. Telehealth interventions in maternity care demonstrate significant benefits such as reduced travel costs, decreased waiting time, and improved access in rural or underserved areas. For health care workers, telehealth supports timely antenatal education, early detection of complications through remote monitoring (e.g., blood pressure and weight), and enhanced patient engagement via mobile applications. The COVID-19 pandemic has accelerated the use of virtual antenatal consultations, creating opportunities for nursing professionals to extend their role in health promotion, psychosocial support, and counseling. However, challenges persist technological barriers, inequitable access, patient trust issues, and limitations in replacing physical examinations with virtual care raise concerns about patient safety. Telehealth in maternity care holds promise for advancing practices through innovations like tele-ultrasound, remote blood pressure surveillance, self-monitoring of fundal height, and digital maternal health education platforms. Yet, barriers related to equity, nurse preparedness, provider adoption, and regulatory frameworks must be addressed. Collaborative, research and policy support are essential to harness the full potential of telehealth, ensuring safe, equitable, and holistic care for pregnant women and their families.